Characterization of nickel plated copper heat spreaders with different catalytic activation processes for flip-chip ball grid array package - Lim V.; Ahmad I.; Seng F.C.; Amin N.; Rasid R. (2023)
This paper presents the effects of two different catalytic activation techniques on the thermal performance of flip chip heat spreaders. The two activation techniques investigated are i) thin nickel-copper strike and ii) galvanic initiation. Thermal diffusivity of these heat spreaders was studied using the Nano-flash Apparatus [1]. High temperature storage tests were run to investigate the extent of intermetallic diffusion between the nickel and copper layers. The results obtained showed that heat spreaders processed with thin nickel-copper strike catalytic activation technique formed thick nickel-copper intermetallic layers compared to those processed with galvanic initiation. Nickel-copper intermetallic layers have lower thermal conductivity compared to pure copper [2]. As a result, heat spreaders processed with thin nickel copper strike have lower thermal diffusivity values averaged at 35-65W/mK XX compared to 60-85W/mK YY measured for those processed with galvanic-initiation. It is also discovered that the nickel-copper intermetallic layers of these heat spreaders grew thicker from 0.2?m at initial time until around 0.55?m after high temperature storage of 168 hours, further degrading the thermal diffusivity of these heat spreaders. As a conclusion, the galvanic initiation technique provides better thermal performance for heat spreaders used in semiconductor packages.